Determination of Stability Constants of Some Bivalent Metal Complexes of 2-Amino-5-Methyl-Benzene Thiol - Sharma, Bhavna; Bhagchandani, Pushpa (Asian Journal of Chemistry, 2010)
The successive stability constants of the complexes of 2-amino-5-methyl benzenethiol with various bivalent transition metal cations have been determined in (60% v/v) acetone-water mixture at 25 ± 0.1ºC and constant ionic strength μ = 0.1 M (NaCl) by adopting the pH titration technique of Irving and Rossotti1.